Amyloid-like aggregation influenced by lead(II) and cadmium(II) ions in hen egg white ovalbumin. (March 2023) - Mijin, Nemanja; Milošević, Jelica; Stevanović, Sanja; Petrović, Predrag; Lolić, Aleksandar; Urbic, Tomaz; Polović, Natalija
Abstract: The aggregation of proteins into fibrillar, amyloid-like aggregates generally results in an improved, positive effect on various techno-functional properties within food products, such as gelation, emulsification, and foam stabilization. These highly stable structures, characterized by their repetitive, β-sheet rich motifs, may develop as the result of the thermal treatment of protein-rich food products. Heavy metal ions can influence amyloid-like aggregation of food proteins. Lead(II) and cadmium(II) represent some of the most abundant and common environmental water and food pollutants. In this work, the influence of heavy metal ions, lead and cadmium on amyloid-like aggregation of ovalbumin at high temperatures (90 °C) and under acidic conditions (pH 2.0) was investigated. Ovalbumin is used as a general model for how heavy metals can affect amyloid-like aggregation of a food protein. Structural changes were monitored via Thioflavin T and 8-Anilino-1-naphthalenesulfonic acid fluorescence, Fourier-Transform infrared spectroscopy, atomic force microscopy, dynamic light scattering, as well as computational analyses. The obtained results indicate that the added heavy metal ions bind to different sites within ovalbumin prior to thermal treatment. Lead binding sites are closer to the hydrophobic regions of an protein, while cadmium ion binding sites are more exposed. This specific binding of metal ions affects the morphologies of amyloid-like aggregates, resulting in lead-induced branching of amyloid-like fibrils, or cadmium-induced tangling of fibrils into dense amyloid clusters. This additive effect of heavy metal ions is most evident in ovalbumin samples which contain a mixture of both heavy metal ions. Graphical abstract: Image 1 Highlights: Ovalbumin amyloid aggregates further cluster in the presence of cadmium and lead ions. Cadmium and lead ions preferentially bind to different sites in ovalbumin. Lead binding induced branching and clustering of amyloid-like aggregates. Cadmium binding results in the tangling and clustering of amyloid-like aggregates.